Stretching One’s Legs: Free Word-Groups vs Idioms - P.S. Dronov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The article deals with a corpus-based case study of two somatic/gesture/movement idioms containing the constituent legs, namely Russian protânut’ nogi (to die) and English to stretch one’s legs (to walk around and loosen one’s leg muscles after sitting down or lying down for a time). Using the Russian National Corpus, the Corpus of Contemporary American English, and British National Corpora, the author has studied the idiom modifications, variations of their figurative meanings, as well as has raised the question of cultural specificity regarding the choice of their underlying metaphors. The author has arrived at a number of conclusions, most notably at the following: the more transparent and obvious the connection between the two and the original gesture is, the more often homonymous free wordgroups occur, being virtually identical for the two languages in spite of the differences between the original metaphors. One has to bear in mind, however, that despite the presence of a connection between a somatic/gesture/movement idiom and its original gesture or movement, this connection sometimes may not seem obvious to a speaker. The data of text corpora have revealed that the idiom to stretch one’s legs is more common in British English rather than in its American counterpart; however, the homonymous free word-group is more frequent in the corpora regardless of the language variety.